The Effectiveness of a SAVI-Based Teaching Module on Arabic Language at Madrasah Aliyah Ismailiyah Jombang - Wati, Ani Rohmah; Hidayah, Nurul; Aisa, Aufia; Wilwadikta, Qur’ani Parang (Borneo Journal of Language and Education, 2026)
Despite decades of formal Arabic instruction in Indonesia, many Madrasah Aliyah students still struggle due to unprepared teachers and monotonous, non-contextual teaching materials. This study aims to analyze the effectiveness of teaching materials based on the Somatic, Auditory, Visual, Intellectual (SAVI) approach in improving Arabic language learning outcomes at Madrasah Aliyah Ismailiyah. Through a collaborative method that optimizes all sensory modalities, the SAVI approach is designed to create a fun, independent, and flexible learning environment. This research employs a quantitative approach with a pre-experimental design, specifically the One Group Pretest - Posttest model. The sample included the entire population through saturated sampling. Data collection was primarily conducted through pre-test and post-test instruments, supplemented by observation and documentation to provide context. The research instruments underwent rigorous testing for validity, reliability, item difficulty, and discrimination power. Data analysis was performed using normality tests as a prerequisite, followed by a Paired Sample T-Test to determine significance and an N-Gain test to measure the effectiveness of the teaching materials. The results of the N-Gain analysis indicate that the use of SAVI-based teaching materials significantly improved learning outcomes, with an effectiveness percentage of 79.80%, categorized as "effective." These findings indicate that the SAVI approach is an effective alternative for improving Arabic instruction at the Madrasah Aliyah level.